Assessment of Proteinase and Phospholipases Enzymes Isolated from Pathogenic Candida species from Women Attending Antenatal Clinic at Mbeya Zonal Referral Hospital, Southern Highland Regions of Tanzania - Chaula, Y; Swilla, JD; Lyatuu, F; Namkinga, L A. (Journal of Biology and Life Science, 2024)
Fungi are a global cause of vaginal infections, with vaginal candidiasis largely afflicting tropical regions including most parts of sub-Saharan Africa. In Tanzania, baseline studies have established the prevalence of Candida species among symptomatic and asymptomatic pregnant women in Dar es Salaam (Namkinga et al., 2005; Namkinga 2012) and in Mwanza (Mushi et al., 2019). However, no study that has been done to determine the above-mentioned enzymes form Candida species in Southern Highland Regions of Tanzania. Several factors have been reported to contribute to the virulence and pathogenicity of Candida, among others the production of extracellular hydrolytic enzymes, particularly phospholipase and proteinase. Therefore, this study was designed to investigate the in vitro production of phospholipases and proteinases enzymes from isolated pathogenic Candida spp from pregnant women. Of the 280 samples collected from symptomatic and asymptomatic pregnant women attending antenatal clinics at Mbeya Zonal Referral Hospital were tested for several microbiological methods such as the wet mount microscopic preparations (hanging drop) and the Gram stained smears for microscopy, cultures on Sabouraud’s dextrose agar and on Conidia enhancing medium (Corn meal agar), germ tube test, biochemical tests, sugar fermentation-assimilation tests and molecular test to characterize Candida species. Phospholipase production was performed in egg yolk medium while the production of proteinase was done in a medium containing bovine serum albumin. All analyses were performed in triplicates. The results showed that; out of the 280 tested, 155 (74.3%) isolates were phospholipase positive while 201 (96.6%) were positive for proteinase activity. C. albicans was the species with the highest number of positive isolates for proteinase and phospholipase 110 (95.6%), and most strains of C. albicans produce both enzymes (phospholipases and proteinases). The non-albicans Candida isolates were also producers of hydrolytic enzymes that, consequently, might be able to cause infections as favorable conditions arises.